2012
DOI: 10.1364/ol.37.000437
|View full text |Cite
|
Sign up to set email alerts
|

Passively mode locked femtosecond Tm:Sc_2O_3 laser at 21 μm

Abstract: We report on the passive mode locking of a Tm 3 :Sc 2 O 3 laser at 2.1 μm using a semiconductor saturable absorber mirror based on InGaAsSb quantum wells. Transform-limited 218 fs pulses are generated with an average power of 210 mW. A maximum output power of 325 mW is produced during mode locking with the corresponding pulse duration of 246 fs at a pulse repetition frequency of 124.3 MHz. A Ti:sapphire laser is used as the pump source operating at 796 nm. © 2012 Optical Society of America OCIS codes: 140.405… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Utilizing Tm 3+ (1%):Sc 2 O 3 as the gain material, SESAM mode-locked pulses as short as 218 fs with a spectral bandwidth of more than 20 nm have been realized at 210 mW of average output power and 120 MHz repetition rate under Ti:sapphire pumping [79]. In these experiments a filter ensured laser operation beyond 2050 nm to match the emission of the laser to the saturable absorption characteristics of the absorber.…”
Section: B Mode Locking Of Tm 3+ -Doped Sesquioxides Around 2 μMmentioning
confidence: 99%
“…Utilizing Tm 3+ (1%):Sc 2 O 3 as the gain material, SESAM mode-locked pulses as short as 218 fs with a spectral bandwidth of more than 20 nm have been realized at 210 mW of average output power and 120 MHz repetition rate under Ti:sapphire pumping [79]. In these experiments a filter ensured laser operation beyond 2050 nm to match the emission of the laser to the saturable absorption characteristics of the absorber.…”
Section: B Mode Locking Of Tm 3+ -Doped Sesquioxides Around 2 μMmentioning
confidence: 99%
“…Various approaches have recently been pursued to extend the spectral coverage of frequency combs into the mid-infrared [10]. Direct approaches include new laser gain materials for modelocked solid-state and fiber lasers [11][12][13] or semicon-ductor devices such as quantum cascade lasers [14,15]. Another approach relies on exploiting different aspects of nonlinear optics, such as supercontinuum generation (SCG) in fibers [16][17][18] and waveguides [19][20][21], or Kerr comb generation in microresonators [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Mode-locking and Q-switching are two common methods to generate pulse laser [1]- [8]. Most of the reported mode-locked Tm-doped pulse lasers are realized by passive mode-locking, using semiconductor saturable absorber mirror (SESAM) [1]- [4] or graphene saturable absorber (GSA) [5], [6]. As for active mode-locking, Eckerle et al reported an actively mode-locked Tm-doped fiber laser based on bulk optics component using acousto-optic modulator (AOM) [8].…”
Section: Introductionmentioning
confidence: 99%